Mast cell activation may contribute to adverse health transitions in COVID-19 patients with frailty - Xiangqi Li; Chaobao Zhang; Zhijun Bao (Emerging Microbes and Infections)
A prominent aspect of the post-coronavirus disease-2019 (post-COVID-19) era is long-COVID. Therefore, precise patient classification and exploration of the corresponding factors affecting long-COVID are crucial for tailored treatment strategies. Frailty is a common age-related clinical syndrome characterized by deteriorated physiological functions of multiple organ systems, which increases susceptibility to stressors. Herein, we performed an inclusion and exclusion analysis (definite COVID-19 infection diagnosis, clear underlying disease information, ≥60 years old, and repeated sampling of clinical cases) of 10,613 blood samples and identified frailty cases for further investigation. RNA-Seq data were used for differential gene expression and functional and pathway analyses. The results revealed that patients with frailty were more prone to poor health conversions and more sequelae, and the blood transcriptome had obvious disturbances in pathways associated with immune regulation, metabolism, and stress response. These adverse health transitions were significantly associated with mast cell activation. Additionally, NCAPG, MCM10, and CDC25C were identified as hub genes in the peripheral blood differential gene cluster, which could be used as diagnostic markers of poor health conversion. Our results indicate that healthcare measures should be prioritized to mitigate adverse health outcomes in this vulnerable patient group, COVID-19 patients with frailty, in post-COVID era.